The relationship between parental depression and child internalizing and externalizing problems: The roles of parenting stress and child maltreatment - Chen, Chen (Frontiers in Public Health, 2023)
Although the relationships between parental mental health and child behavior problems have been explored by previous studies, the pathways between these two variables are still unclear. The present study aims to explore the relationships between parental depression and child behavior problems, and to examine the roles of parenting stress and child maltreatment in those relationships in the Chinese cultural context. Data were collected from 855 Chinese families with preschool-aged children, and mediation analysis was used to examine the pathways between these variables. The results showed that parental depression positively predicted child behavior problems, and child maltreatment and the combination of parenting stress and child maltreatment mediated the relationships between parental depression and child behavior problems, respectively. These findings suggest that parental depression not only have a direct effect on child behavior problems, but also have an indirect effect via parenting stress and child maltreatment. Decreasing the levels of parenting stress and child maltreatment should be applied in interventions to break the relationships between parental depression and child behavior problems under the Chinese cultural context.